Exploratory Descriptive on the Self-Confidence of Prospective Accountants Toward Economic Digitalization - Anisa Kusumawardani; Dhian Andanarini Minar Savitri; Aurel Ariandrani (Jurnal Akuntansi, 2024)
One of the key characteristic features of change in the modern socio-economic environment is information, which manifested in both the dynamic development of the information within the communication technology and in the transformation of the information itself into a strategic resource for the entities’ welfare, especially for an economic entity inside the turbulence of an ever-changing world. Accounting is considered one of the fragments that is significantly impacted by the speeding up of digital transformation. Academics and practitioners have noted several difficulties and issue that comes to the surface concerning the decline of accounting functionality and the reporting value of the information for stakeholders. The existence of new technological capabilities such as artificial intelligence does not eliminate the possibility of alteration on the role of an accountant, and this can create tension for students majoring in accounting. Whether it is a threat or an opportunity for accounting development for the 'generation Z’ facing the AI era. The existing volatility assessment of the future accounting profession has contributed to the decline in motivation of the current generation to see the prestige of the accounting profession, and negatively affected the demand for accounting education. This study examines how future accountants undergo formal education in the face of the digital accounting era, provide actionable recommendations for individuals and organizations to build and maintain self-confidence in the context of Industry 5.0. The analysis used in this study is qualitative methods with phenomenological approaches analyze with QSR NVivo12 which leads to the conclusion that the current vision and role of an accountant who was previously called a record holder must develop to a bigger role that possesses a certain influence within the present-day market and society. The function of an accountant cannot be fully automated, due to the wide variety of accounting functions that require professional judgment based on systems of expertise, experience, and intuition. By achieving a comprehensive vision and role, the acceleration of accounting information technology will require the role of an accountant and not vice versa.